Sites of gastrointestinal lesion induced by mycophenolate mofetil: a comparison with enteric-coated mycophenolate sodium in rats - Yichen Jia; Rulin Wang; Long Li; Ying Zhang; Jiawei Li; Jina Wang; Xuanchuan Wang; Guisheng Qi; Ruiming Rong; Ming Xu; Tongyu Zhu (BMC, 2018)
Abstract Background Immunosuppressant drugs for renal transplant mycophenolate mofetil (MMF) and enteric-coated mycophenolate sodium (EC-MPS) cause gastrointestinal (GI) disorders. The specific site of GI tract targeted by MMF and EC-MPS remains unclear. Methods In this study, we investigated the effects of MMF and EC-MPS on stomach, duodenum, jejunum, ileum, colon and rectum using a rat model. Rats were randomized into five groups: control, MMF (100 mg/kg·d), mofetil (30 mg/kg·d), EC-MPS (72 mg/Kg·d), mofetil + EC-MPS. Each group was treated with drugs once a day for 7 days through intra-gastric gavage. Diarrhea grade of each rat were measured every day, as well as the body weight. Blood was collected by tail nick and Seven days later, the rats were sacrificed, GI tissues were collected for Histological research. Results The results showed that diarrhea grade and weight loss were significantly higher in MMF group than other groups. The pathological score of MMF group was significantly higher than EC-MPS group and EC-MPS + mofetil group in jejunum and ileum tissues, but not other segments of GI tract. Absorption of EC-MPS is delayed, compared to that of MMF. MPAG concentration in duodenum, jejunum and ileum tissues of MMF group is higher than EC-MPS group. Mofetil may increase the magnitude of MPA absorption. Conclusions Our data suggested that MMF might target jejunum and ileum and induce GI injury. EC-MPS causes less injury in GI tract than MMF, probably due to its kinetic property.